Structure and functional divergence of PIP peptide family revealed by functional studies on PIP1 and PIP2 in Arabidopsis thaliana - Yu, Xiao-song; Wang, Hong-run; Lei, Fei-fan; Li, Rui-qi; Yao, Hui-peng; Shen, Jin-bo; Ain, Noor-ul; Cai, Yi (Frontiers in Plant Science, 2023)
PAMP-induced secreted peptide (PIP), one of the small post-translationally modified peptides (PTMPs), plays a crucial role in plant development and stress tolerance. However, little is known about functional divergence among this peptide family. Here, we studied the evolution of the PIP family in 23 plant species (10 monocotyledons and 13 dicotyledons from 7 families) and their functional divergence in Arabidopsis. A total of 128 putative PIP precursors were identified and classified into two subfamilies through phylogenetic analysis. Functional studies on AtPIP1 which represents Clade I family and AtPIP2 which represents Clade II family have shown that AtPIP2 displayed stronger immunity induction activity but weaker root growth inhibition than AtPIP1 in Arabidopsis. Transcriptome analysis of Arabidopsis seedlings treated with AtPIP1 and AtPIP2 showed that differential genes for both polypeptides were significantly enriched in similar plant defense pathways. However, Co-expression and Protein-protein interaction (PPI) analysis showed that the functions of AtprePIP2 co-expressed genes were more enriched in plant defense pathways than AtprePIP1. Molecular docking results show that AtPIP1 binds to RLK7 receptor with a more stable free energy and less binding area than AtPIP2, while hydrogen bond transfer occurs at the SGP motif position. The above results suggest that the PIP family have undergone functional divergence during evolution. Collectively, this work illustrates the relationship between PIP structure and function using Arabidopsis PIP as an example, and provides new insights into the current understanding between growth inhibition and immune responses which may be correlated but not fully coupled.